2022
DOI: 10.1038/s41598-022-16839-3
|View full text |Cite
|
Sign up to set email alerts
|

Canopy-cooling systems applied on avocado trees to mitigate heatwaves damages

Abstract: With climate change, spring heatwaves have become frequent in the Mediterranean region. High temperatures combined with wind and low humidity are problematic for subtropical crops adapted to high humidity and mild climate. Avocado is a valuable crop—nutritionally and economically—and many new orchards are planted in Mediterranean areas. Spring heatwaves increase avocado fruitlets dropping, severely decreasing yields. Addressing and solving the problem are necessary to maintain the crop's profitability. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This approach led to water intake growing exponentially with the decrease in avocado leaf temperature; it also reduced g S rates, enlarging the average fruit size. In this context, Lazare et al [143] reported that in avocado orchards in a semi-arid region in Israel, the use of sprinklers to cool the canopy during spring heat waves after flowering was able to reduce leaf temperatures by 10 • C. This outcome significantly decreased water stress and increased avocado fruit yields by 8-12%.…”
Section: Plant Physiological Response To Water Stressmentioning
confidence: 99%
“…This approach led to water intake growing exponentially with the decrease in avocado leaf temperature; it also reduced g S rates, enlarging the average fruit size. In this context, Lazare et al [143] reported that in avocado orchards in a semi-arid region in Israel, the use of sprinklers to cool the canopy during spring heat waves after flowering was able to reduce leaf temperatures by 10 • C. This outcome significantly decreased water stress and increased avocado fruit yields by 8-12%.…”
Section: Plant Physiological Response To Water Stressmentioning
confidence: 99%